Tuning chain topologies and magnetic anisotropy in one-dimensional cobalt(ii) coordination polymers via distinct dicarboxylates. Issue 21 (17th May 2022) - Tian, Zhengfang; Moorthy, Shruti; Xiang, Huan; Peng, Peng; You, Maolin; Zhang, Qian; Yang, Shun-Yi; Zhang, Yang-Lu; Wu, Dong-Qing; Singh, Saurabh Kumar; Shao, Dong
Abstract : Two 1D Co(ii ) coordination polymers constructed by mixed terpyridine–dicarboxylate bridges were structurally and magnetically characterized to show slow magnetic relaxation, distinct chain topologies, and magnetic anisotropy tuned by dicarboxylates. Abstract : Based on a terpyridine derivative and two different dicarboxylate ligands, two new cobalt(ii ) coordination polymers, namely [Co(pytpy)(DClbdc)] n (1 ) and [Co(pytpy)(ndc)] n (2 ) (pytpy = 4′-(4-pyridyl)-2, 2′:6′, 2′′-terpyridine, H2 DClbc = 2, 5-dichloroterephthalic acid, and H2 ndc = 2, 6-naphthalenedicarboxylic acid), were hydrothermally synthesized and characterized structurally and magnetically. Single-crystal X-ray diffraction revealed that 1 and 2 are one-dimensional (1D) linear and zigzag chain complexes, respectively, with the Co 2+ centers located in a compressed and an elongated bipyramid of 1 and 2, respectively. Magnetic investigation revealed that the chain complexes exhibit distinct easy-axis and easy-plane magnetic anisotropy with D = −95.6 and −42.8 cm −1 for 1 and 2, respectively. The inverse magnetic anisotropy of 1 and 2 was further confirmed and understood using ab initio calculations. Interestingly, field-induced single-ion magnet (SIM) behaviors were evidenced at low temperatures with the effective energy barrier of U eff = 27.3 and 12.7 cm −1 for 1 and 2, respectively. The foregoing results provide not only a way for the construction of 1D cobalt(ii ) coordination polymers with slow magnetic relaxation behavior but also a chance to tune chain topologies and magnetic anisotropy in one-dimensional coordination polymers via different dicarboxylates.